Comics studies here and now - Aldama, Frederick Luis, 1969- (Routledge advances in comics studies, 2018)
Comics Studies Here and Now marks the arrival of comics studies scholarship that no longer feels the need to justify itself within or against other fields of study. The essays herein move us forward, some in their re-diggings into comics history and others by analyzing comics and all its transmedial and fan-fictional offshoots on its own terms. Comics Studies stakes the flag of the arrival as a full-fledged discipline that today and tomorrow excavates, examines, discusses, and analyzes all aspects that make up the resplendent planetary republic of comics. This collection of scholarly essays is a testament to the fact that comic book studies have come into their own as an academic discipline; simply and powerfully moving comic studies forward with their critical excavations and theoretical formulas based on the common sense understanding that comics add to the world as unique, transformative cultural phenomena.